Increasing Student Interest in Learning Islamic Education through the Application of Audio Visual Media Using the Discovery Method at SMAN 4 Probolinggo - Devy Habibi Muhammad; Fitri Kurnia; Hani Nafi’ah Rachmawati; Tanti Setiawati; Khoridatul Bahiyah (STIT Attaqwa, 2023)
In this research, the main problem is the application of audio-visual media using the discovery method which is able to make the PAI learning process run well. By using these media and methods, which are useful for increasing students' interest in learning PAI so that in the learning process that has been designed, educators and students can work together well as expected. The reason for using audio visual media and using the discovery method is because in the current era researchers get research subjects, namely high school students. If as an educator you arenot creative enough in learning then the learning process will not run well. Because high school students tend to get bored and will not focus on learning if the learning process is not interesting. Audio visual learning media, namely learning media, a short film that is suitable for the material and also the discovery method is a method where students must discover new knowledge and concepts for themselves in the learning they are studying. In this research, the researcher conducted Classroom Action Research (PTK) by carrying out two cycles in which the research subjects were in class XI-E, totaling 36 students at SMAN 4 PROBOLINGGO. The research results showed an increase in interest in learning in class XI-E students after using audio-visual media and discovery methods. Therefore, the audio visual media and discovery methods used in learning can be said to be effective and can increase students' interest in learning, so with this the researcher also hopes that in the future educators will be able to use audio visual media and discovery methods in PAI learning because of the media and methods. This can increase students' interest in learning